An ER‐Targeting Iridium(III) Complex That Induces Immunogenic Cell Death in Non‐Small‐Cell Lung Cancer. (4th January 2021) - Wang, Lili; Guan, Ruilin; Xie, Lina; Liao, Xinxing; Xiong, Kai; Rees, Thomas W.; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract: Immunogenic cell death (ICD) is a vital component of therapeutically induced anti‐tumor immunity. An iridium(III) complex (Ir1 ), containing an N, N ‐bis(2‐chloroethyl)‐azane derivate, as an endoplasmic reticulum‐localized ICD inducer for non‐small cell lung cancer (NSCLC) is reported. The characteristic discharge of damage‐associated molecular patterns (DAMPs), that is, cell surface exposure of calreticulin (CRT), extracellular exclusion of high mobility group box 1 (HMGB1), and ATP, were generated by Ir1 in A549 lung cancer cells, accompanied by an increase in endoplasmic reticulum stress and reactive oxygen species (ROS). The vaccination of immunocompetent mice with Ir1 ‐treated dying cells elicited an antitumor CD8 + T cell response and Foxp3 + T cell depletion, which eventually resulted in long‐acting anti‐tumor immunity by the activation of ICD in lung cancer cells. Ir1 is the first Ir‐based complex that is capable of developing an immunomodulatory response by immunogenic cell death. Abstract : Ir1 effectively targets the endoplasmic reticulum of A549 lung cancer cells and triggers the production of ER stress and ROS production. Ir1 was demonstrated to induce multiple characteristics of immunogenic cell death (ICD) both in vitro and in an in vivo vaccination experiment. Ir1 is the first iridium(III) complex to induce ICD in non‐small‐cell lung cancer.